2000
DOI: 10.1038/35002628
|View full text |Cite
|
Sign up to set email alerts
|

The S receptor kinase determines self-incompatibility in Brassica stigma

Abstract: The self-incompatibility possessed by Brassica is an intraspecific reproductive barrier by which the stigma rejects self-pollen but accepts non-self-pollen for fertilization. The molecular/biochemical bases of recognition and rejection have been intensively studied. Self-incompatibility in Brassica is sporophytically controlled by the polymorphic S locus. Two tightly linked polymorphic genes at the S locus, S receptor kinase gene (SRK) and S locus glycoprotein gene (SLG), are specifically expressed in the papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
367
1
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(378 citation statements)
references
References 28 publications
5
367
1
5
Order By: Relevance
“…However, the apparently general use of a polyadenylation signal within the first intron of SRK and SRK-like genes is suggestive of some functional significance for the soluble form of the receptor domain. It is possible that in A. lyrata, as well as in the self-incompatible Brassica plants that lack SLG or express low levels of SLG, the soluble form of SRK fulfills a role similar to that proposed for SLG and functions to enhance the SI response (Dixit et al, 2000;Takasaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the apparently general use of a polyadenylation signal within the first intron of SRK and SRK-like genes is suggestive of some functional significance for the soluble form of the receptor domain. It is possible that in A. lyrata, as well as in the self-incompatible Brassica plants that lack SLG or express low levels of SLG, the soluble form of SRK fulfills a role similar to that proposed for SLG and functions to enhance the SI response (Dixit et al, 2000;Takasaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The function of SLG is not well understood, and its role in SI has been questioned (Cabrillac et al, 1999;Nasrallah, 2000;Nishio and Kusaba, 2000). However, recent studies have indicated that SLG enhances the intensity of the SI response (Takasaki et al, 2000), possibly by contributing to the proper maturation of the SRK receptor and its accumulation to physiologically relevant levels (Dixit et al, 2000).…”
mentioning
confidence: 99%
“…In the SSI system of Brassica , SLG and SRK genes are expressed in the mature papilla cells of the stigma (Nasrallah and Nasrallah 1993 ). The expression of SRK is signifi cantly lower than SLG ; however, SRK plays a key role in the self-pollen recognition of Brassica (Takasaki et al 2000 ). The male S -gene in Brassica , SP11 / SCR , is tightly linked to the SRK gene at the S -locus and is expressed in the anther tapetum (the sporophytic tissue) and microspores at a late developmental stage of pollen grains (Schopfer et al 1999 ;Takayama et al 2000 ;Shiba et al 2002 ).…”
Section: Genes Located At or Near The S -Locus Of I Trifi Damentioning
confidence: 99%
“…Because I. trifi da has the same genetic SI system as Brassica species, it might be expected that products of genes homologous to SLG or SRK would be present in the reproductive tissues of I. trifi da. SRK is known as a female S -gene (Stein et al 1991 ;Takasaki et al 2000 ), and SLG is an S -gene-related gene in Brassica (Kandasamy et al 1989 ). Ipomoea secreted glycoprotein genes ( ISG1 , -2 , and -3 ) were isolated from a mature stigma cDNA library, and the sequences of these genes showed structural similarities to Brassica SLGs.…”
Section: Several Approaches To Identifying S -Genes In I Trifi Damentioning
confidence: 99%
“…The female determinant is S -receptor kinase (SRK) (Takasaki et al 2000 ). SRK consists of an SLG-like extracellular domain, a transmembrane domain, and an intracellular serine/threonine kinase domain.…”
Section: Self/non-self Recognition System In the Brassicaceaementioning
confidence: 99%